2012
DOI: 10.1007/s13277-012-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

RHBDD2: a 5-fluorouracil responsive gene overexpressed in the advanced stages of colorectal cancer

Abstract: In previous studies, we identified rhomboid domain containing 2 (RHBDD2) gene to be markedly overexpressed in breast cancer patients that developed recurrence of the disease. In this study, we evaluated for the first time RHBDD2 gene expression in colorectal cancer (CRC). Five public available DNA microarray studies were compiled in a homogeneous dataset of 906 colorectal samples. The statistical analysis of these data showed a significant increase of RHBDD2 expression in the advanced stages of CRC (p < 0.01).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…More recently, we also observed significant RHBDD2 mRNA and protein overexpression in the advanced stages of colorectal cancer (Lacunza et al 2012), suggesting that RHBDD2 up-modulation might be associated with breast and colon cancer malignant progression. We also determined that RHBDD2 protein expression is upregulated in colon cancer cells treated with the chemotherapeutic agent 5-fluourouracil (5FU) (Lacunza et al 2012), which has recently been shown to be an inducer of ER stress in hepatocellular carcinoma cells (Yadunandam et al 2012).…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…More recently, we also observed significant RHBDD2 mRNA and protein overexpression in the advanced stages of colorectal cancer (Lacunza et al 2012), suggesting that RHBDD2 up-modulation might be associated with breast and colon cancer malignant progression. We also determined that RHBDD2 protein expression is upregulated in colon cancer cells treated with the chemotherapeutic agent 5-fluourouracil (5FU) (Lacunza et al 2012), which has recently been shown to be an inducer of ER stress in hepatocellular carcinoma cells (Yadunandam et al 2012).…”
Section: Introductionmentioning
confidence: 58%
“…In this sense, we recently demonstrated that the chemotherapy agent 5FU treatment on colorectal cancer cells significantly increases RHBDD2 mRNA and protein expression, compared with the untreated cells, suggesting that RHBDD2 up-modulation might be induced as an adaptive cellular response to the 5FU cytotoxic effects (Lacunza et al 2012). Interestingly, a recent study showed that 5FU promotes ER stress, activating the mitochondrial apoptotic cell death process (Yadunandam et al 2012).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors indicate that expression of RHBDD2 significantly increases in advanced stages of colorectal cancer. Also, they found a significant increase of RHBDD2 mRNA and protein after treatment with the chemotherapy agent 5-fluorouracil (41).…”
Section: Discussionmentioning
confidence: 95%